Seven Habits of Islamic Education Teachers as Role Models for Students - Wulandari, Viona Dwi; Habiburrahman, Zaky; Burhanuddin, Burhanuddin (Muaddib: Journal of Islamic Teaching and Learning, 2026)
Islamic Education teachers play a strategic role not only in delivering religious knowledge but also in shaping students’ character through exemplary attitudes and behavior. Their daily habits influence both the learning process and the moral and spiritual development of students. This study analyzes seven key habits of Islamic Education teachers that serve as role models for learners. The research employed a qualitative case study approach, with data collected through in-depth interviews, literature review, and classroom reflections. Thematic analysis was conducted using NVivo 12 to identify consistent behavioral patterns. The findings highlight seven essential habits: punctuality, thorough preparation of lesson materials, enthusiastic teaching, empathetic listening, consistent appreciation, continuous self-development, and exemplary conduct. These habits collectively foster discipline, motivation, confidence, and moral integrity among students. The implications of this study emphasize that adopting such habits strengthens the role of Islamic Education teachers as agents of character building. Schools and educational institutions are encouraged to integrate these practices into teachers’ daily routines to enhance both academic achievement and moral development.